Principles and Characteristics of Random Lasers and Their Applications in Medical, Bioimaging and Biosensing - Kamil, Nur Ain Insyirah Muhamad; Ismail, Wan Zakiah Wan; Ismail, Irneza; Balakrishnan, Sharma Rao; Sahrim, Mus'ab; Suhaimi, Syahida; Juliza Jamaludin; Marinah Othman (Amer Inst Physics, 2024)
A random laser is an optical device that depends on multiple light scattering and gain to provide the feedback mechanism and light amplification respectively. A random laser is different with a regular laser where the regular laser needs a cavity for the feedback mechanism. Multiple light scattering can be considered detrimental in the regular laser but in the random laser, multiple light scattering can increase the path length of light in the active medium. This article studies the operation principles and characteristics of random lasers including the history and applications of the lasers. The theories of light scattering and light amplification are properly explained, followed by a discussion on characteristics of random lasers in terms of random laser emission, emission linewidth and coherence. Furthermore, the unique characteristics of random lasers can contribute to many applications leading to promising element for the future medical and biosensing development.